New approaches to pediatric dilated cardiomyopathy in current practice - Amalia Fagarasan; Maria Oana Sasaran (Amaltea Medical Publishing House, 2020)
Progresses to radiologic and molecular genetics fields created the premisses for the development of a new, descriptive classification system of cardiomyopathies, known under the MOGE (S) acronym, with the help of informations provided by molecular genetic testing that led to better knowledge regarding their physiopathogenic backgrounds, the implementation of a descriptive, nosologic phenotype-genotype and the establishment of an accurate clinic and genetic diagnosis. Dilated cardiomyopathy (DCM) in children remains the most frequent type of cardiomyopathy, representing an important cause of death in the first 2 years of life, and its impact at neonatal age is not fully understood, due to the low number of studies regarding its real incidence. Its death rate is high, 10 % of neonatal deaths of cardiac origin being caused by DCM. Ecocardiography helps in establishing the diagnosis and evolution and therapy monitoring. Modern ultrasound techniques (tissue Doppler or speckle tracking), as well as 3D ultrasound provide highly accurate data. Paraclinic assessments, such as neuropeptides (BNP, NT-proBNP), have both diagnostic and prognostic roles. Medical treatment recommended for congestive cardiac failure symptom relief consists of angiotensine converting enzyme inhibitors (the long acting ones are preffered - Lisinopril), mineralocorticoid receptors antagonists and beta-blockers (Bisoprolol), which act by decreasing the afterload, limiting the ventricular remodelation process and can easily be administered, in unique dose. Novel therapeutic approaches have aroused, such as regenerative therapy of cardiomyocytes. Cardiac transplant remains a therapeutic option limited by a small number of donors. Conclusions. Diagnostic and therapeutic approach of DCM have been substantially improved, integration in current practice of new diagnostic methods and regenerative therapeutic approaches can change the prognostic perspective of this disease.